Optimalisasi Pelaksanaan Pembinaan Narapidana dalam Merubah Perilaku Warga Binaan : (Studi di Lembaga Pemasyarakatan Pemuda Kelas III Langkat) - Sarah Febyola; Mhd. Azhali Siregar; Abdul Razak Nasution (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Optimization of the justification for the establishment of prisoner guidance so far, is based on policies that maintain the types of criminal penalties as regulated in Article 10 of the Criminal Code. Prisoner guidance is one type of sanction in criminal law that is often used as a means to overcome crime problems. The use of prisoner guidance as a means to punish perpetrators of criminal acts began in the late 18th century which was based on the ideology of individualism and the humanitarian movement. Prisoner guidance increasingly plays an important role and shifts the position of the death penalty and corporal punishment which are considered cruel.In general, the image of prison is a very scary place, not getting good food, sleeping on the floor and being bitten by mosquitoes, there is torture and it is very uncomfortable, it is difficult to communicate with the outside world and family, there is no entertainment and suffering and limited in everything. Teguh Prasetyo, explained that prison gives an image to the general public, as a place where criminals are deprived of their freedom and tortured and employed or trained so that they can form good behavior and character after leaving prison. Therefore, the image was changed to prisoner development. The image of prison that gives a scary image to the general public, aims to provide a deterrent element for criminals, so that they become aware and change their evil attitudes and behavior. Based on the background above, the following problem formulation is determined: How to Optimize the Implementation of Prisoner Development in Changing Behavior Towards Inmates?. This research is an empirical legal research, which examines the optimization of the implementation of prisoner guidance in changing the behavior of inmates carried out at the Class III Langkat Youth Penitentiary. The implementation of empirical legal research aims to see the empirical conditions of the optimization of the implementation of prisoner guidance in changing the behavior of inmates at the Class III Langkat Youth Penitentiary, as well as its influence on changes in prisoner behavior.